2008
DOI: 10.5688/aj720222
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Pharmacy Students' Decision to Pursue a Doctor of Pharmacy Degree

Abstract: Objectives.To determine what influenced pharmacy students to pursue a career in pharmacy and how those influences varied among different racial groups. Methods. A 30-question survey instrument was developed and administered to doctor of pharmacy (PharmD) students at the University of Georgia and Florida A&M University. Data were analyzed to identify differences between students at different institutions and of different racial groups. Results. Most students were encouraged by someone to pursue pharmacy. Studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 4 publications
8
46
0
1
Order By: Relevance
“…Work experience is a factor influencing prepharmacy and professional student attitudes. 8,10,13,14 The first objective of the study was to assess prepharmacy students' perceptions of the professional role of pharmacists prior to students' enrollment in pharmacy school using the theory of planned behavior and professional commitment constructs. Theory of planned behavior questions resulted in average scores between 2 and 3 (agree to strongly agree) on the majority of questions, demonstrating student knowledge of the professional roles of pharmacists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Work experience is a factor influencing prepharmacy and professional student attitudes. 8,10,13,14 The first objective of the study was to assess prepharmacy students' perceptions of the professional role of pharmacists prior to students' enrollment in pharmacy school using the theory of planned behavior and professional commitment constructs. Theory of planned behavior questions resulted in average scores between 2 and 3 (agree to strongly agree) on the majority of questions, demonstrating student knowledge of the professional roles of pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many students have experience in a hospital or community pharmacy setting before entering pharmacy school. 8,10 Work experience is a factor influencing student attitudes toward pharmaceutical care, career aspirations, and application to pharmacy school. 8,[10][11][12][13][14][15] In a study by Siracuse and colleagues, work experience was positively associated with career aspirations of becoming a patient care pharmacist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] However, these choices may be made without much knowledge or consideration of what constitutes a career in pharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson and colleagues found that the most important factor in a student's decision to pursue a pharmacy degree was the influence of family members. 4 Knowing a pharmacist was the second strongest factor, followed by prior work experience in a pharmacy setting. Career-day events, however, were found to have little influence on a student's decision to pursue a pharmacy career.…”
Section: Introductionmentioning
confidence: 99%